Prevention of Panton-Valentine Toxin-Mediated Leucocyte Destruction Depending on the Ultra-Diluted Staphylococcinum Potency Gradient - Goswami, Pritam; Ghosh, Sayak; Ali, Sk Swaif; Basu, Anamika; Khanra, Joydeep; Ghosh, Shubhamoy; Das, Satadal (Homœopathic Links, 2020)
Background Panton-Valentine toxin (PVT) is an important pathological marker of staphylococcal infection mediated by functional as well as morphological damage of the phagocytic cells. Human body being an ecological niche for the bacteria shows higher affinity toward staphylococcal infection. A steady escalation in mortality and morbidity associated with antibiotic resistance in gram-positive infections is an emerging threat all over the globe; thus, it is important to find out an alternative strategy that can diminish the virulence and pathogenicity of the bacteria. Staphylococcin is a colicin-type chemical secreted by Staphylococcus aureus helps to prevent growth of organisms other than its progenitor. In this study, we evaluated the efficacy of homoeopathic medicine Staphylococcinum against staphylococcal PVT at different potencies (6CH, 12CH, 30CH and 200CH).Materials and Methods Different potencies of Staphylococcinum were administered in a leucocyte buffy coat preparation infected with staphylococcal suspension (0.5 McFarland's standard) along with control with alcohol. They were kept in incubator for 2 hours and then centrifuged at 1200 rpm for 5 minutes. Smears prepared on slides with centrifuged deposits stained by Preston and Morrell's modified Gram's method of staining and evaluated under the microscope.Results It was observed that there was extensive destruction of leukocytes in control and 6CH potency, while the degree of destruction decreased markedly from 12CH to 200CH. At 200CH potency, leukocytes were almost normal, which clearly indicate the preventive action of Staphylococcinum against PVT. The mean percentages of intact leucocytes were 0.73, 0.93, 10.00, 27.67 and 65.00 in control, 6CH, 12CH, 30CH and 200CH potencies, respectively.Conclusion The finding may help in the use of this medicine in moribund patients in cases of disseminated S. aureus infection as there is no known side effect of the medicine. However, in vivo study is necessary before such use in those cases.
Keywords: Staphylococcus aureus; Panton-Valentine leucocidins; Staphylococcinum; antibiotic resistance; homeopathy